Changes in Vibrio natriegens Growth Under Simulated Microgravity - Yin, Man; Ye, Bingyu; Jin, Yifei; Liu, Lin; Zhang, Yan; Li, Ping; Wang, Yahao; Li, Ye; Han, Yanping; Shen, Wenlong; Zhao, Zhihu (Frontiers in Microbiology, 2020)
The growth rate of bacteria increases under simulated microgravity (SMG) with low-shear force. The next-generation microbial chassis Vibrio natriegens (V. natriegens ) is a fast-growing gram-negative, non-pathogenic bacterium with a generation time of less than 10 minutes. Screening of a V. natriegens strain with faster growth rate was attempted by two-week continuous long-term culturing under SMG. However, the rapid growth rate of this strain made it difficult to obtain the desired mutant strain with even more rapid growth. Thus, a mutant with slower growth rate emerged. Multi-omics integration analysis was conducted to explore why this mutant grew more slowly, which might inform us about the molecular mechanisms of rapid growth of V. natriegens instead. The transcriptome data revealed that whereas genes related to mechanical signal transduction and flagellin biogenesis were up-regulated, those involved in adaptive responses, anaerobic and nitrogen metabolism, chromosome segregation and cell vitality were down-regulated. Moreover, genome-wide chromosome conformation capture (Hi-C) results of the slower growth mutant and wide type indicated that SMG-induced great changes of genome 3D organization were highly correlated with differentially expressed genes (DEGs). Meanwhile, whole genome re-sequencing found a significant number of structure variations (SVs) were enriched in regions with lower interaction frequency and down-regulated genes in the slower growth mutant compared with wild type (WT), which might represent a prophage region. Additionally, there was also a decreased interaction frequency in regions associated with well-orchestrated chromosomes replication. These results suggested that SMG might regulate local gene expression by sensing stress changes through conformation changes in the genome region of genes involved in flagellin, adaptability and chromosome segregation, thus followed by alteration of some physiological characteristics and affecting the growth rate and metabolic capacity.